Theoretical aspects of concepts internal labor migrant, internal labor migration, state regulation of internal labor migration (Journal of Economic Research & Business Administration, 2018)
The article describes the concepts of internal labor migrant, internal labor migration, state regulationof internal labor migration and analyzes the definitions given by scientists to these concepts. The authorpoints out that in Kazakhstan the concept of an internal labor migrant is not fully used in its meaning,and, in legislative acts and concepts, there is no differentiation of this concept from an internal migrant.Also, the article describes the concept and types of internal labor migration as one of the type of labormigration, also the author expresses his opinion on the theoretical substantiation of some types of internallabor migration. The author shares his opinion about the uselessness of the translation of termsmigration, internal migration into the Kazakh language and their preservation as international terms. Thearticle analyzes theoretical aspects of state regulation of internal labor migration, the author considersthe opinions of various domestic and foreign authors on this issue. The policy of the Republic of Kazakhstanin the field of regulation of internal labor migration is considered and its gaps are noted. The authorraises the issue of the need to form a new state concept and a new legal framework in the field of stateregulation of internal labor migration. In conclusion, the author brings forward his definition of conceptsinternal labor migrant, internal labor migration, state regulation of internal labor migration